Efficacy of a multiple-component and multifactorial personalized fall prevention program in a mixed population of community-dwelling older adults with stroke, Parkinson's Disease, or frailty compared to usual care: The PRE.C.I.S.A. randomized controlled trial - La Porta, Fabio; Lullini, Giada; Caselli, Serena; Valzania, Franco; Mussi, Chiara; Tedeschi, Claudio; Pioli, Giulio; Bondavalli, Massimo; Bertolotti, Marco; Banchelli, Federico; D'Amico, Roberto; Vicini, Roberto; et al. (Frontiers in Neurology, 2022)
Background: Fall risk in the elderly is a major public health issue due to the injury-related consequences and the risk of associated long-term disability. However, delivering preventive interventions in usual clinical practice still represents a challenge. Aim: To evaluate the efficacy of a multiple-component combined with a multifactorial personalized intervention in reducing fall rates in a mixed population of community-dwelling elderly compared to usual care. Design: Randomized Controlled Trial (NCT03592420, clinicaltrials.gov). Setting: Outpatients in two Italian centers. Population: 403 community-dwelling elderly at moderate-to-high fall risk, including subjects with Parkinson's Disease and stroke. Methods: After the randomization, the described interventions were administered to the intervention group (n=203). The control group (n=200) received usual care and recommendations to minimize fall risk factors. In addition, each participant received a fall diary, followed by 12 monthly phone calls. The primary endpoint was the total number of falls in each group over 12 months secondary endpoints were other fall-related indicators recorded at one year. Participants' functioning was assessed at baseline (T1) and 3-month (T3). Results: 690 falls were reported at 12 months, 48.8% in the intervention and 51.2% in the control group, with 1.66 (± 3.5) and 1.77 (± 3.2) mean falls per subject, respectively. Subjects with ≥ 1 fall and ≥2 falls were, respectively, 236 (58.6%) and 148 (36.7%). No statistically significant differences were observed between groups regarding the number of falls, the falling probability, and the time to the first fall. According to the subgroup analysis, no significant differences were reported. However, a statistically significant difference was found for the Mini-BESTest (p=0.004) and the Fullerton Advanced Balance Scale (p=0.006) for the intervention group, with a small effect size (Cohen's d 0.26 and 0.32, respectively), at T1 and T3 evaluations. Conclusions: The intervention was ineffective in reducing the number of falls, the falling probability, and the time to the first fall at 12 months in a mixed population of community-dwelling elderly. A significant improvement for two balance indicators was recorded in the intervention group. Future studies are needed to explore different effects of the proposed interventions to reduce falls and consequences.